Synthesis and biological evaluation of 4, 6-diaryl-2-pyrimidinamine derivatives as anti-breast cancer agents. Issue 6 (1st April 2018) - Liu, Linyi; Tang, Zhichao; Wu, Chengze; Li, Xinyu; Huang, Ali; Lu, Xiang; You, Qidong; Xiang, Hua
Graphical abstract: Highlights: Approximate 50% of patients with ER-positive tumors either initially do not respond or become resistant to SERMs. Tamoxifen simulated the cell line Ishikawa's proliferation under the concentration of 10 µM in our experiment. A series of designed 4, 6-diaryl-2-pyrimidinamine derivatives could simultaneously antagonize ER and inhibit VEGFR-2. Abstract: Breast cancer is the most frequently diagnosed cancers and the leading causes of cancer death among females worldwide. Estrogen receptor positive has been identified as the predominant internal reasons, involving in more than 70% breast cancer patients and SERMs which competes with estradiol for the binding to ERα in breast tissue are widely used in the treatment of ER+ breast cancer, such as tamoxifen, raloxifene. However, many SERMs may cause negative side effects due to their estrogenic activity in other tissues and approximate 50% of patients with ER-positive tumors either initially do not respond or become resistant to these drugs. Here, a series of designed 4, 6-diaryl-2-pyrimidinamine derivatives had been synthesized to treat estrogen receptor positive breast cancer by simultaneously antagonizing ER and inhibiting VEGFR-2. Bioactivity evaluation showed that these compounds could significantly inhibit the proliferation of MCF-7, HUVEC and Ishikawa cells. Further studies identified compoundIII-3A could antagonize against estrogen action and inhibit the phosphorylation of VEGFR-2 as well as inhibit angiogenesis in vivo. The results indicated designed 4, 6-diaryl-2-pyrimidinamine derivatives can be used to further study as anti-breast cancer drugs.